Neglected Archive: Museum Collections of Locally Forged Hoes as Evidence of Contributions by Women to the Agricultural Economy of the Phongolo-Mzimkhulu Region Prior to the Twentieth Century - Kotze, Steven (The Journal of Natal and Zulu history, 2021)
A 2018 survey conducted in eight KwaZulu-Natal museums determined that field-hoes, called amageja in Zulu, constitute less than one-fifth of locally forged metallurgical items in those archives, while the rest are weapons. Crucially, only two displays related to either Iron Age history or the Zulu Kingdom in the museums that were evaluated provide contextual information on field-hoes. In this article I contend that gender-based divisions of labour in nineteenth-century African communities of this region have affected attitudes towards the tools they used. As groups of objects are generally assembled within collections in relation to other categories, Bourdieu suggested that the value of an artefact can only be established after investigation of the 'history of the procedure of canonisation and hierarchisation' of any particular object type. Investigating the place of amageja in museums, this research considers the largely overlooked cultural and economic significance of such items, including evidence of attitudes towards agriculture preserved in oral testimony from African sources and Zulu-language idioms. The article argues that museum collections of hoes form a neglected archive of 'hoe cultivation', or subsistence crop production based on the use of manual implements, within the Phongolo-Mzimkhulu geographic region that roughly approximates to the modern territory of KwaZulu-Natal.